PENYELESAIAN SISTEM PERSAMAAN DIFERENSIAL LINIER MELALUI DIAGONALISASI MATRIKS - Edy Sarwo Agus Wibowo; Yuni Yulida; Thresye Thresye (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2013)
This paper discusses the application of matrix diagonalization to determine the general solution of a system of first order homogeneous linear differential equations. Furthermore, if the matrix of the system is not diagonalizable then the solution is determined through the fundamental matrix.